Penerapan Rima dan Chant sebagai Sarana Pembelajaran Kreatif - Irmawaty Umar; Magvirah El Walidayni Kau (Dedikasi Mandiri Nusantara, 2026)
Introducing English to early childhood learners requires engaging and age-appropriate learning activities that can stimulate their interest and active participation. At an early stage of language learning, children need opportunities to listen to, recognize, imitate, and produce English sounds through meaningful and enjoyable activities. Rhymes and chants can serve as creative learning media because they combine sound patterns, rhythm, repetition, and verbal interaction, which are suitable for young learners. This community service program, entitled “Applying Rhymes and Chants as Creative Media for Introducing English Sounds to Early Childhood Learners,” was conducted at SDN 91 Kota Gorontalo. The program aimed to introduce basic English sounds and simple vocabulary through enjoyable activities using rhymes and chants. The implementation consisted of several stages, including initial observation, preparation of learning materials, implementation of rhymes and chants-based activities, and evaluation. During the activities, the children listened to and repeated English words and expressions, practiced selected sounds, and participated in rhythmic activities accompanied by simple movements. The activities were designed to provide repeated exposure to English sounds while creating an enjoyable and participatory learning environment. The implementation demonstrated that rhymes and chants encouraged children to participate actively, imitate English sounds and words, and engage enthusiastically in the learning activities. The use of rhythm and repetition also provided children with meaningful opportunities to become familiar with the sound patterns of English. Therefore, rhymes and chants can be utilized as simple, creative, and enjoyable media for introducing English sounds to early childhood learners.